Territorial development, tourism, and the protection of World Heritage Sites: issues of geopolitical conflict - Mark Bailoni (Via@)
This paper uses critical geopolitical analysis to examine local conflicts over development projects that could threaten the environment, economic development, and/or landscape amenities of UNESCO World Heritage Sites. In particular, it examines the case of the contested construction of a hydroelectric dam in Portugal, close to the Alto Douro Wine Region, a World Heritage Site. Tourism issues are key in sites where the World Heritage listing, which can bring substantial revenue, is threatened by a development project. These development disputes are primarily conflicts of interest between various stakeholders, acting at different scales and defending their own concerns and perceptions, from local protesters to state representatives on the World Heritage Committee. As with other types of conflict, World Heritage listing reinforces the planning conflict by generating multiple interests, responding to contradictory functional, heritage, landscape, and identity considerations.